Teaching Speaking Skills Using the Spinning Wheel Game in Senior High School - Razan; Siti Maria Ulfa (Penerbit STKIP PGRI Bangkalan, 2025)
Students in Senior High School still have some difficulty speaking English fluently. The researcher of this study investigated the students' speaking skills by using the Spinning Wheel Game media. In this study, the researcher used a qualitative method with a case study design. The researcher focuses on the student’s fluency in the English language. The primary data of this study are from observations and the results of the interviews; meanwhile, the secondary data are from books, journals, personal documents, and official written documents. The instruments used in this study are field note observations, an interview guide, and documentation. The purpose of this study is to investigate the use of the Spinning Wheel Game in teaching speaking skills and to examine students' responses to using the Spinning Wheel Game. The result of this study showed that the Spinning Wheel Game helps students in the class. The students were active, enthusiastic, and focused on the material, and they comprehended it well. The Spinning Wheel Game media also helps students improve their fluency and confidence in speaking the English language.